Mitochondrial and Peroxisomal Alterations Contribute to Energy Dysmetabolism in Riboflavin Transporter Deficiency. (13th August 2020) - Colasuonno, Fiorella; Niceforo, Alessia; Marioli, Chiara; Fracassi, Anna; Stregapede, Fabrizia; Massey, Keith; Tartaglia, Marco; Bertini, Enrico; Compagnucci, Claudia; Moreno, Sandra
Abstract : Riboflavin transporter deficiency (RTD) is a childhood-onset neurodegenerative disorder characterized by progressive pontobulbar palsy, sensory and motor neuron degeneration, sensorineural hearing loss, and optic atrophy. As riboflavin (RF) is the precursor of FAD and FMN, we hypothesize that both mitochondrial and peroxisomal energy metabolism pathways involving flavoproteins could be directly affected in RTD, thus impacting cellular redox status. In the present work, we used induced pluripotent stem cells (iPSCs) from RTD patients to investigate morphofunctional features, focusing on mitochondrial and peroxisomal compartments. Using this model, we document the following RTD-associated alterations: (i) abnormal colony-forming ability and loss of cell-cell contacts, revealed by light, electron, and confocal microscopy, using tight junction marker ZO-1; (ii) mitochondrial ultrastructural abnormalities, involving shape, number, and intracellular distribution of the organelles, as assessed by focused ion beam/scanning electron microscopy (FIB/SEM); (iii) redox imbalance, with high levels of superoxide anion, as assessed by MitoSOX assay accompanied by abnormal mitochondrial polarization state, evaluated by JC-1 staining; (iv) altered immunofluorescence expression of antioxidant systems, namely, glutathione, superoxide dismutase 1 and 2, and catalase, as assessed by quantitatively evaluated confocal microscopy; and (v) peroxisomal downregulation, as demonstrated by levels and distribution of fatty acyl β -oxidation enzymes. RF supplementation results in amelioration of cell phenotype and rescue of redox status, which was associated to improved ultrastructural features of mitochondria, thus strongly supporting patient treatment with RF, to restore mitochondrial- and peroxisomal-related aspects of energy dysmetabolism and oxidative stress in RTD syndrome.